1994
DOI: 10.1159/000113626
|View full text |Cite
|
Sign up to set email alerts
|

Cell Types in the Mustached Bat Auditory Cortex

Abstract: Cells in the auditory cortex of the mustached bat were studied with Golgi stains. No cell types appeared to be unique to the mustached bat auditory cortex or to specialized functional areas, but the laminar proportions and distributions of cell types were somewhat different from that reported for primary sensory cortex of other species. Two major cell types were distinguished, those with dendritic spines and those without spines. Non-spiny neurons were concentrated deep in layer IH/TV and in layer V, and had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
3
27
1
Order By: Relevance
“…Spiny cells that are not stellate or pyramidal are occasionally encountered here but, as a group, do not display consistent anatomical or physiological features that might allow them to function as auditory cortical versions of the visual spiny stellates. Our data, combined with anatomical evidence from previous Golgi studies in several species, indicate that the spiny stellate is not the predominant or even a major cell type in any auditory thalamocortical recipient zone studied (McMullen and Glaser, 1982;Meyer and Ferres-Torres, 1984;Winer, 1984;Fitzpatrick and Henson, 1994).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Spiny cells that are not stellate or pyramidal are occasionally encountered here but, as a group, do not display consistent anatomical or physiological features that might allow them to function as auditory cortical versions of the visual spiny stellates. Our data, combined with anatomical evidence from previous Golgi studies in several species, indicate that the spiny stellate is not the predominant or even a major cell type in any auditory thalamocortical recipient zone studied (McMullen and Glaser, 1982;Meyer and Ferres-Torres, 1984;Winer, 1984;Fitzpatrick and Henson, 1994).…”
Section: Discussionsupporting
confidence: 53%
“…Rose's observation may have foreshadowed observations of fundamental differences between layer 4 in auditory and other sensory cortices. Golgi studies in rabbit (McMullen and Glaser, 1982), cat (Winer, 1984), mustached bat (Fitzpatrick and Henson, 1994), and human (Meyer and Ferres-Torres, 1984;Meyer et al, 1989) showed that spiny stellates are rare in layer 4. In contrast to the symmetric dendritic trees of visual and somatosensory spiny stellates that are confined to layer 4, a great variety occurs in the dendritic arborization patterns of these infrequently encountered cells purported to be spiny stellate homologues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This insectivore (suborder: Tenrecomorpha;Eisenberg 1981;Piccinini et al 1991;McPhee and Novacek 1993), was shown to have one of the lowest neocorticalization indices (Stephan et al 1991). In contrast to monotremes, marsupials and most other placental mammals, Echinops telfairi does not exhibit any granularization indicative of the presence of a lamina IV throughout its entire neocortex (Rehkämper 1981;Garey et al 1985;Rowe 1990;Glezer et al 1993;Fitzpatrick and Henson 1994;Krause and Saunders 1994;Nieuwenhuys 1994;Harman et al 1995). In this species, furthermore, some non-neocortical regions, such as the entorhinal and prepiriform cortices and the hippocampus, are characterized by a trilaminar architecture, with one main cellular layer situated between two layers consisting predominantly of neuropil.…”
Section: Introductionmentioning
confidence: 89%
“…In the literature, there appears to be little agreement on whether these bifurcating apical branches are characteristic of bitufted (Bartesaghi et al 2003), multiapical (Ferrer et al 1986a, b), or even extraverted pyramidal neurons (Fitzpatrick and Henson 1994). Although resembling layer II extraverted pyramidal neurons in several other species (hedgehog, bat, and opossum: Sanides and Sanides 1972;dolphin: Glezer and Morgane 1990;quokka: Tyler et al 1998; humpback whale: Hof and Van der Gucht 2007; giant elephant shrew, giant and lesser anteater: Sherwood et al 2009), elephant superficial pyramidal neurons did not meet the strict definition of extraversion, whereby apical dendritic extent exceeds that of basilar dendrites (Sanides and Sanides 1972).…”
Section: Elephant Superficial Pyramidal Neurons and Human Supragranulmentioning
confidence: 99%